2015
DOI: 10.1080/03081060.2014.997449
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the effects of congestion on fuel economy for advanced power train vehicles

Abstract: Fuel-speed curves (FSC) are used to account for the aggregate effects of congestion on fuel consumption in transportation scenario analysis. This paper presents plausible FSC for conventional internal combustion engine (ICE) vehicles and for advanced vehicles such as hybrid electric vehicles, fully electric vehicles (EVs), and fuel cell vehicles (FCVs) using a fuel consumption model with transient driving schedules and a set of 145 hypothetical vehicles. The FSC shapes show that advanced power train vehicles a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 8 publications
0
9
0
1
Order By: Relevance
“…This simplification is reasonable for the purpose of this study. In general, congestion causes a greater decline in the onroad fuel economy of low efficiency powertrains and has a smaller effect on or even increases that of high efficiency and electric-drive vehicles (30). Therefore, we expect greater energy savings if more low efficiency vehicles, such as pick-ups, SUVs, and commercial vehicles, make up the congested vehicle mix, and we expect smaller benefits if a larger share of high efficiency and electric- drive vehicles is assumed.…”
Section: Sensitivity Analysismentioning
confidence: 95%
“…This simplification is reasonable for the purpose of this study. In general, congestion causes a greater decline in the onroad fuel economy of low efficiency powertrains and has a smaller effect on or even increases that of high efficiency and electric-drive vehicles (30). Therefore, we expect greater energy savings if more low efficiency vehicles, such as pick-ups, SUVs, and commercial vehicles, make up the congested vehicle mix, and we expect smaller benefits if a larger share of high efficiency and electric- drive vehicles is assumed.…”
Section: Sensitivity Analysismentioning
confidence: 95%
“…AVs will have the ability to coordinate with other vehicles and infrastructures (V2V and V2I) at the intersection, to improve the traffic flow and reduce the crash frequency that will result in less energy use and less GHG emission [ 22 ]. Bigazzi and Clifton’s study indicated that internal combustion engines (ICEs) fail to maintain fuel efficiency in slow-moving traffic at a speed of 30 miles per hour or lower [ 60 ]. In contrast, Gas electric hybrid vehicles are less sensitive to speed variations and retain fuel efficiency roughly at 20 mph.…”
Section: Causes Of Reduction In Ghg Emissionsmentioning
confidence: 99%
“…The energy consumptions are constant among arcs and are unrelated to the arc length and the traffic state. However, in practice, EVs may become more fuel efficient as the average speed increases, particularly at local arterials [28]. To the best of our knowledge, only Goeke and Schneider and Lin et al computed consumptions over actual road networks while considering the parameters and loads of the EV [29,30].…”
Section: Literature Reviewmentioning
confidence: 99%